Efficacy and safety of anticoagulation in atrial fibrillation patients with intracranial hemorrhage: A systematic review and meta-analysis - Zhou, Qiang; Liu, Xiang; Yang, Xian; Huang, Xiao-Hui; Wu, Yan-Zi; Tao, Ying-Ying; Wei, Meng (Frontiers in Pharmacology, 2023)
Background: The benefits and risks of starting anticoagulation therapy, such as non-vitamin K antagonist oral anticoagulants or warfarin, in atrial fibrillation (AF) patients with a history of intracranial hemorrhage (ICH) remain controversial. We performed a systematic review and meta-analysis to compare the safety and efficacy of starting oral anticoagulation (OAC) and non-oral anticoagulation in these patients. Methods: PubMed, Cochrane Library, and Embase were searched from inception to 01 May 2022 for randomized controlled trials and cohort studies, reporting effectiveness and safety outcomes for anticoagulation therapy in AF patients with ICH. The Newcastle-Ottawa Scale (NOS) and the Cochrane Collaboration tool were used to evaluate bias risks for all randomized controlled trials (RCTs) and cohort studies. An effects model was applied to calculate adjusted hazard ratios (aHRs) for RCTs and cohort studies. Results: We analyzed data from two RCTs (304 patients) and seven Cohort studies (17,477 patients). Compared to non-OAC, starting OAC therapy reduced the risk of Ischemic Stroke/SE (aHR: 0.64, 95% CI: 0.55–0.57) and all-cause death (aHR: 0.53, 95% CI: 0.35–0.80) in AF patients and a prior history ICH. Starting OAC therapy did not increase the risk of recurrent ICH (aHR: 1.07, 95% CI: 0.66–1.74), but increased the risk of major bleeding (aHR: 1.38, 95% CI: 1.00–1.91) than no OAC therapy. The non-vitamin K antagonist oral anticoagulants (NOACs) had a lower risk of Ischemic Stroke/SE (aHR: 0.84, 95% CI: 0.70–1.00), recurrent ICH (aHR: 0.63, 95% CI: 0.49–0.82), and all-cause death (aHR: 0.65, 95% CI: 0.48–0.88) compared to warfarin. According to subgroup analyses, starting OAC therapy have a higher risk of recurrent ICH than non-OAC therapy (aHR: 1.57, 95% CI: 1.36–1.81) for Asians. Conclusions: After ICH in AF patients, restarting or initiating OAC therapy decreased the risk of Ischemic Stroke/SE and all-cause death but did not increase the risk for recurrent ICH. NOACs have better efficacy and safety than warfarin if OAC therapy is started. However, starting OAC increases the risk for recurrent ICH in the Asian region.